2006 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--596
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions About Rate Processes: Preliminary Evidence For The Importance Of Emergent Conceptual Schemas In Thermal And Transport Sciences

Abstract: is professor of chemical engineering at the Colorado School of Mines where he has taught chemical engineering and interdisciplinary courses and conducted research in educational methods for the past twenty years. He has received three university-wide teaching awards and has held a Jenni teaching fellowship at CSM. He has received grant awards for educational research from the National Science Foundation, the U.S. Department of Education (FIPSE), the National Endowment for the Humanities, and the Colorado Commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Misconceptions are prevalent in thermal and fluid sciences and persist even among advanced engineering students (Miller, Streveler, Yang, & Santiago Román, 2011). For example, more than 50% of engineering students' responses to questions on heat transfer were in clear violation of the Second Law of Thermodynamics (Miller, Streveler, Olds, et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Misconceptions are prevalent in thermal and fluid sciences and persist even among advanced engineering students (Miller, Streveler, Yang, & Santiago Román, 2011). For example, more than 50% of engineering students' responses to questions on heat transfer were in clear violation of the Second Law of Thermodynamics (Miller, Streveler, Olds, et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it can be difficult to attribute cause and effect relationships (Webb, Senocak, & Yang, 2014), and as a result, students often tend to mistake emergent processes with sequential processes. Traditionally, most emergent concepts are explained in the language of sequential processes (Miller, Streveler, Olds, et al, 2006), which may create misconceptions for students. Table 1 presents some distinctions between the two kinds of processes according to Chi's (2006) schema framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study described in this paper extends ongoing work to identify difficult concepts in thermal and transport science [12] and measure students' understanding of those concepts via a concept inventory [5,6,7]. The present work focuses on two fundamental areas of engineering: engineering mechanics (statics, strength of materials, and dynamics), and electric circuits, which are complementary to thermal and transport science.…”
Section: Introductionmentioning
confidence: 91%
“…As the conceptual framework to answer this question, we use the work of Reiner, Slotta, Chi, and Resnick [7] who posited that fundamental concepts like force, voltage, and current may be difficult for students to learn because students view those processes as if they were substances. Reiner et al called this propensity to view processes as substances a "substance-based schema" and listed 11 attributes which are mistakenly applied to processes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…students came to a conclusion that was in clear violation of the 2 nd law of thermodynamics. 1 In addition, undergraduate engineering students who had received several semesters of physics instruction still hold fundamental misconceptions of force and momentum. [17][18] Although literarily thousands of studies have reported student misconceptions in all areas of science and engineering, most have not contributed to the fundamental question: how can the misconception be repaired to promote deep fundamental understanding of key engineering and science concepts?…”
Section: Evolving New and Difficult Processes In Engineeringmentioning
confidence: 99%